THE RELATIONSHIP BETWEEN FAMILY MOTIVATION AND COMPLIANCE WITH HAEMOGLOBIN EXAMINATION CONTROL FOR PREGNANT WOMEN IN THE THIRD TRIMESTER AT POSYANDU TANGGUL KULON: THE RELATIONSHIP BETWEEN FAMILY MOTIVATION AND COMPLIANCE WITH HAEMOGLOBIN EXAMINATION CONTROL FOR PREGNANT WOMEN IN THE THIRD TRIMESTER AT POSYANDU TANGGUL KULON - Ila, Lailatul Zahroh; ernawati; Melati (LPPM Universitas dr. Soebandi, 2024)
Keywords: Family Motivation, Compliance of Pregnant Women ABSTARCT Background : One of the factors that influences pregnant women is compliance with haemoglobin examination is motivation. Family participation in providing motivation can increase positive energy for pregnant women so that it can increase pregnant women is compliance in carrying out hemoglobin tests. Pregnant women is compliance with hemoglobin examination can determine an early diagnosis. Purpose : To determine the relationship between family motivation and compliance with haemoglobin examination control for third trimester pregnant women at posyandu tanggul kulon. Methods : This research uses a correlation analytical research design, to look for a causal relationship between two variables. The approach uses a cross sectional with a population of 30 pregnant women in the third trimester. The sampling technique uses total sampling. The instruments used for family motivation were questionnaires and compliance control for third trimester pregnant women's hemoglobin examination by looking at the KIA book data. The analysis used is the Spearman rank statistical test. Results : From the results of calculations using the spearman rank test spss 23.0, the results obtained were ρ-value 0,003 < α 0,05. Conclusions : Based on the results of the Spearman Rank test, it shows that there is a relationship between family motivation and compliance with control of hemoglobin examinations for third trimester pregnant women at Posyandu Tanggul Kulon in 2024. It is hoped that the family will further increase the motivation of pregnant women ini the trimester III to carry out haemoglobin examinations so that they can prevent pregnancy complications.